Clinical profile of patients admitted to a specialized COVID ICU of a reference public hospital in the metropolitan region of São Paulo (Research, Society and Development, 2024)
Studies show that during the COVID-19 pandemic, several hospitals in Brazil became a reference for care for patients with symptoms characteristic of SARS-CoV-2. Objective: to analyze the clinical profile of patients admitted to the Intensive Care Unit (ICU) of a reference hospital for the care of patients with COVID-19 in the metropolitan region of São Paulo. Method: A retrospective, observational, cross-sectional quantitative analysis study was carried out with 42 medical records of COVID-positive patients. Results: As a result, the majority were male (57.1%), presenting as a comorbidity during hospitalization pneumonia (61.9%), diabetes mellitus (40.5%), systemic arterial hypertension (31%) and obesity (28.6%). Regarding clinical interventions, all patients received antibiotic therapy and ventilatory support, with an average length of stay of 20.6 days (SD = 15.9) and an outcome of death of 66.67%. Conclusion: During the pandemic, the clinical profile of patients treated at the institution studied showed a high degree of severity and complexity requiring qualified multidisciplinary care.